The role of digital media in promoting cultural exchange of the language of effective dialogue and supporting peaceful coexistence on the Instagram platform in the Kingdom of Bahrain (المجلة الدولية للبحوث العلمية, 2025)
The current study presents the role of digital media in promoting cultural exchange of the language of effective dialogue and its support for peaceful coexistence in the kingdom of Bahrain and  the effectiveness of the Instagram platform in crystallizing this interaction between individuals among themselves and its impact on supporting peaceful coexistence, and aims to identify the nature of digital media and its impact on promoting cultural exchange and the ability of dialogue to enhance communication between individuals through the Instagram platform and support peaceful coexistence among individuals. Bahraini society. where the descriptive survey approach was used, and we selected the available sample represented by members of the Bahraini society consisting of (52) individuals, and they were selected (29) males and (23) females to perform the questionnaire in the analysis of the study and interviews. The study reached several results, the most important of which is that the intensity of exposure to Instagram contributes to enhancing cultural exchange and enhancing the language of dialogue between individuals. Supporting peaceful coexistence among members of bahraini society it also recommended the need to pay attention to the importance of digital media and its various means, and to encourage more scientific research that encourages building more tolerant, open and understanding societies in Bahraini societies.